Characterization of TET and IDH gene expression in chronic lymphocytic leukemia: comparison with normal B cells and prognostic significance - Van Damme, Michaël (Clin Epigenetics, 2016)
BACKGROUND: Chronic lymphocytic leukemia (CLL) is the most common hematological malignancy in western countries, characterized by a heterogeneous clinical course. Although genetic studies have identified chromosomal aberrations or specific mutations, epigenetic changes have been poorly characterized in CLL. METHODS: We assessed ten-eleven translocations (TET) 1, 2, and 3, isocitrate dehydrogenase (IDH) 1, and 2 messenger RNA (mRNA) expression using real-time PCR on purified leukemic B cells from 214 CLL patients (median follow-up = 75 months, range 1–380), normal peripheral blood B cells (n = 20), and umbilical cord blood B cells (n = 21). The microenvironment influence was assessed after 24 h co-culture of CLL cells with bone marrow mesenchymal stromal cells (BMSC). Finally, 5-hydroxymethylcytosine level (%5-hmC) was assessed by ELISA in CLL cells alone or with microenvironment stimuli. RESULTS: TET 1 and 3 and IDH2 were decreased in CLL cells compared with healthy B cells (P = 0.0221, 0.0013, <0.0001, respectively), while IDH1 was overexpressed (P = 0.0037). TET2 and IDH1 were significantly correlated with treatment-free survival (TFS); patients with high TET2/IDH1 expression had a higher median TFS (111 months) than patients with low expression (78 months, P = 0.0071/0.0123). Moreover, TET1 expression decreased (P = 0.0371), while TET3 and IDH2 expression increased (P = 0.0273/0.0039) in co-cultures. However, %5-hmC was not correlated with clinical data and was unchanged following microenvironment stimuli. CONCLUSIONS: Despite a slight deregulation in CLL cells compared with normal B cells, we identified a significant association between TET/IDH gene expression and prognosis, suggesting that epigenetic changes could potentially be associated with disease progression. Moreover, despite an identical %5-hmC, TET gene expression was influenced by contact with BMSC confirming the crucial role of the microenvironment in CLL pathogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13148-016-0298-y) contains supplementary material, which is available to authorized users.